2007
DOI: 10.1016/j.jenvrad.2006.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Elevated concentrations of primordial radionuclides in sediments from the Reedy River and surrounding creeks in Simpsonville, South Carolina

Abstract: Abstract.A gamma-ray survey and analysis of sixteen riverbed samples from the Reedy River watershed near Simpsonville, SC were conducted and compared with national and international studies of primordial radionuclides. The study reported here follows on a recent discovery of anomalously high uranium concentrations in several private well waters in the area near Simpsonville, SC. A HPGe spectrometer was used for quantification of gamma emitting radionuclides in the sediments. All sediments contained radionuclid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 12 publications
0
16
2
Order By: Relevance
“…The mean concentration of 40 K is 0.91 times the world average value (420 Bq/kg) and 0.96 times Indian average value (400 Bq/kg) [6], respectively. The measured concentrations of 238 U and 232 Th (present study) are lower than the values obtained for the Danube river [24], Nile river [9] and Reedy river [16] sediments. However, the concentration of 232 Th in the present study is similar to the values registered by Descamps and Foulquier [25] and Powell et al [16] for French and Reedy river, respectively.…”
Section: Radioactivity Nature Of the Sedimentcontrasting
confidence: 90%
See 3 more Smart Citations
“…The mean concentration of 40 K is 0.91 times the world average value (420 Bq/kg) and 0.96 times Indian average value (400 Bq/kg) [6], respectively. The measured concentrations of 238 U and 232 Th (present study) are lower than the values obtained for the Danube river [24], Nile river [9] and Reedy river [16] sediments. However, the concentration of 232 Th in the present study is similar to the values registered by Descamps and Foulquier [25] and Powell et al [16] for French and Reedy river, respectively.…”
Section: Radioactivity Nature Of the Sedimentcontrasting
confidence: 90%
“…The measured concentrations of 238 U and 232 Th (present study) are lower than the values obtained for the Danube river [24], Nile river [9] and Reedy river [16] sediments. However, the concentration of 232 Th in the present study is similar to the values registered by Descamps and Foulquier [25] and Powell et al [16] for French and Reedy river, respectively. El-Gamal et al [9] and Chowdhury et al [26] have obtained the lower concentration of 40 K in river sediments when compared with present study (Table I).…”
Section: Radioactivity Nature Of the Sedimentcontrasting
confidence: 90%
See 2 more Smart Citations
“…Knowledge about the distribution of the radioactivity present in natural materials enables one to assess any possible radiological hazard to mankind by the use of such materials. Radiation exposures due to naturally occurring radionuclides in sediments including river sediments (building materials) have been studied by many workers (El-Arabi et al, 2006;Narayana et al, 2007;El-Gamal et al, 2007;Powell et al, 2007;Krmar et al, 2009;Al-Hamarneh and Awadallah, 2009;Ramasamy et al, 2004, 2006aand Taskin et al, 2009) all around the world. They were reported that the all studied values are lower than the recommended values.…”
Section: Introductionmentioning
confidence: 99%